3D genomic regulation of lncRNA and Xist in X chromosome. (June 2019) - Yan, Furong; Wang, Xiangdong; Zeng, Yiming
Abstract: Long noncoding RNAs (lncRNAs) act as important regulators in cardiovascular diseases, neural degenerative disease, or cancers, by localizing and spreading across chromatins. lncRNA can regulate the 3D architecture of the enhancer cluster at the target gene locus, relevant to analogous lncRNA-protein coding gene pairs. X inactive specific transcript (Xist) plays a critical role in the process and biological function of lncRNAs. The lncRNA Jpx, Xist activator, is a nonprotein-coding RNA transcribed from a gene within the X-inactivation center and acts as a numerator element to control X-chromosome number and activate Xist transcription by interacting with CCCTC-binding factor. Up-regulated lncRNA Xist initiates X chromosome inactivation process and attracts specific chromatin modifiers. A number of chromatin-modified factors interact with lncRNAs modify 3D genome architecture and mediate Xist function in embryo development. Thus, the regulation of lncRNAs in 3D genome progresses is the key mechanism of Xist, as a therapeutic potential for Xist associated diseases.